Evaluating Learning Motivation: An Analysis of Students' Engagement in Online Learning Environments - Karyadi, Prita Atria; Paristiowati, Maria (Journal of Educational Management and Learning, 2024)
This study analyzes students' learning motivations, including concentration, curiosity, enthusiasm, independence, readiness, encouragement, consistency, and self-confidence during online learning at Pahoa High School. Using a qualitative descriptive method, the research was conducted from February to April 2022, involving 53 students from class XI. Data were collected through observations, interviews, reflective journals, and questionnaires adapted from various research journals, focusing on learning motivation. The data analysis involved stages of data reduction, coding, presentation, and conclusion. Results were categorized into three areas: (1) student learning motivation during online learning, (2) advantages of online learning, and (3) disadvantages of online learning. Questionnaire data revealed that 78% of students exhibited excellent concentration, 57% had good curiosity, 41% displayed fair enthusiasm, 92% showed excellent independence, 54% demonstrated good readiness, 93% had excellent encouragement, 78% maintained excellent consistency, and 61% had good self-confidence. Overall, 69% of students were found to have good learning motivation. These findings suggest that students generally possess strong learning motivations in an online learning environment, providing valuable insights for educators to enhance online teaching strategies and improve student learning outcomes. This study also serves as a reference for future research on learning motivation in online education.